Frictional conditions of AA5251 aluminium alloy sheets using drawbead simulator tests and numerical methods - Trzepieciński, Tomasz (Strojniški vestnik, 2014)
This article presents research results on the effect of sheet metal surface roughness, lubricant conditions and sample orientation on the value of friction coefficient in the drawbead region of sheet metal-forming processes. Aluminium alloys with different temper conditions were used as test materials. The experimental results have ascertained several relationships showing the effect of surface profile and lubrication on the value of the friction coefficient. Based on experimental measurements, it may be concluded that the sample orientation and the lubrication conditions are crucial variables influencing the value of the coefficient of friction. Furthermore, a numerical model of the drawbead has been created in Msc.MARC Mentat software, and several simulations have been performed to study the stress/strain state in stretched sample during drawbead simulator tests. Both isotropic and anisotropic material models were used in the simulations taking into account the sample orientation with respect to the rolling direction of the sheet.
Keywords: koeficienti trenja; preoblikovanje pločevine; simulacije MKE; trenje; zavorne letve